Enhancing Teacher Leadership to Improve Teachers’ Job Performance: A Case of Foreign Languages Department, Fundamental Education School (FES), Beijing Polytechnic (BP) - Zhang, Ping; Fernando, Maria Socorro (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
The purpose of this study was to improve teachers’ job performance through enhancing teacher leadership with a four-month Organization Development Intervention (ODI) program in Foreign Languages Department, FES, BP. BP is a Vocation Education and Training (VET) college. This study employed mixed research methodology to study the outcomes and effectiveness of ODI program. 32 language teachers participated the program, responded the questionnaire at pre and post ODI stages, and 15 informants out of 32 participants answered interview questions after ODI. The objectives were to assess the current situation of teacher leadership in terms of teacher leadership awareness, teacher leadership knowledge, teacher leadership skills and teacher leadership collaboration; to design appropriated ODI activities and implement; to determine the significant difference of each variable between pre-ODI and post-ODI according to research findings; and to design future training plan based on juxtaposed results. Quantitative results presented significant differences comparing data at pre and post ODI stages in terms of teacher leadership awareness, teacher leadership knowledge, teacher leadership skills, teacher leadership collaboration, and teachers’ job performance. Qualitative results provided ODI reflection and deeper insights. Juxtaposed quantitative and qualitative results generated future training plan. Hence, this study concluded that teachers’ job performance could be improved through enhancing teacher leadership. Research hypotheses were tested. Implications of this study and recommendations for future training plan were discussed.